Potential of an asymmetrical agitation in industrial mixing - Kazuhiko Nishi; Naoki Enya; Kazufumi Sonoda; Ryuta Misumi; Meguru Kaminoyama (International Journal of Science and Engineering, 2013)
Mixing is one of the most fundamental operations in chemical engineering. Stirred tanks are widely used in the manufacture of such materials as chemicals, paints, inks, electronics materials, ceramics, foods, pharmaceuticals and cosmetics. Suitable mixing is indispensable to the purpose achievement of a process. Eccentric mixing, in which an impeller installed at eccentric position in a vessel, is one of the traditional methods of promoting mixing. An asymmetrical flow which occurs in vessel is complicated, and it promotes mixing, distribution, and mass transfer. In this study, a new mixing method which eccentric mixing using a large type impeller which attracts attention in recent years is shown. The high performance of a large impeller can be combined with the advantages of an eccentric impeller by using the impeller at an eccentric position. The power consumption and mixing time for MAXBLEND, which is a type of large impeller, were investigated. The power consumption, P, and mixing time, θM, were measured under various eccentric conditions. The relation between the power number (Np) and Reynolds number (Re) and that between the dimensionless mixing time (nθM) and Re were investigated. When eccentric mixing is used industrially, we should be concerned about the horizontal load to a agitating shaft. The large oscillating horizontal load causes serious problems, such as the falling off of the impeller or the breakage of the motor, mechanical seal or gearbox. It is, therefore, important to understand the relation between these values and the impeller rotational speed when designing the mixing equipment and determining the operating conditions. In this study, the torque and horizontal load were measured in eccentric mixing under various eccentric conditions. The averages of both, the torque and the horizontal load, and their standard deviations, corresponding to the amplitude of fluctuation, were shown.Doi: 10.12777/ijse.5.2.73-80 [How to cite this article: Nishi, K., Enya, N., Sonoda, K., Misumi, R., Kaminoyama, M.  (2013). Potential of an asymmetrical agitation in industrial mixing. International Journal of Science and Engineering, 5(2),73-80. Doi: 10.12777/ijse.5.2.73-80]